Aquagenic pruritus in an adolescent effectively managed with β‐alanine supplementation. Issue 1 (10th November 2020) - Friedlander, Mollie S. H.; Admani, Shehla
Abstract: Aquagenic pruritus is a rare debilitating condition, which can be idiopathic, iatrogenic, or associated with systemic disease. In idiopathic cases, treatment can be challenging as options are limited and of variable efficacy. Here, we report the case of a teenage boy with refractory idiopathic aquagenic pruritus effectively managed with administration of β‐alanine supplementation, a treatment gaining traction in lay media but not yet reported in the medical literature. This report adds to the limited options published for treatment of idiopathic aquagenic pruritus in pediatric patients.